Is Radial Deviation of Wrist Related With Median Nerve Swelling in Patients With Rheumatoid Arthritis? A Radiographic, Ultrasonographic, and Electroneuromyographic Study - Başak MANSIZ-KAPLAN; Seçil PERVANE-VURAL; Ömer Faruk ÇELİK and F. Figen AYHAN (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate whether or not radial deviation developing after wrist involvement of rheumatoid arthritis (RA) is a cause of median nerve swelling. Patients and methods: The study included 51 RA patients (12 males, 39 females; mean age 50.9±8.9 years; range, 18 to 65 years) without carpal tunnel syndrome (CTS) detected by electroneuromyography. Duruöz hand index, visual analog scale, and painDETECT questionnaire were performed in clinical assessment. Radiographic measurements including radial inclination (RI) angle were performed. Using ultrasonography, the median nerve cross-sectional areas (CSAs) were measured from the four levels of the distal one third of the forearm, radioulnar joint, pisiform bone, and hook of hamate, while the ulnar nerve CSAs were measured from the pisiform bone. Results: The study was completed with 102 hands of 51 patients. A negative correlation was found between the RI and the median CSAs measured from the radioulnar joint (R=-0.49; p=0.00), the pisiform bone (R= -0.45; p=0.00), and hook of hamate (R= -0.60, p=0.00). When the hands were divided into three groups according to the ranges of RI specified in the literature, the median nerve CSA was found to be significantly higher in the group with low RI at these levels (p<0.001). Conclusion: In patients with RA without CTS, the increase in the median nerve CSAs may be associated with radiographic measures such as radial deviation.